Implementasi Etika Bisnis Islam dalam Transaksi Jual Beli pada Pedagang Pasar Tradisional di Desa Mainan Kecamatan Sembawa Kabupaten Banyuasin - Rahmadi, Firdaus; Nuraida, Nuraida; Walian, Anang (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The efforts of traders at the Toy Village Traditional Market in providing services to buyers must be carried out properly, apply business ethics and establish friendship. The research entitled "Implementation of Islamic Business Ethics in Buying and Selling Transactions at Traditional Market Traders in Toy Village, Sembawa District, Banyuasin Regency". The research objective was to determine the implementation of Islamic business ethics in buying and selling transactions at traditional market traders in Toy Village, Sembawa District, Banyuasin Regency to determine the implementation of Islamic business ethics in buying and selling transactions at traditional market traders in Toy Village, Sembawa District, Banyuasin Regency. This type of research is qualitative research. Data collection techniques include observation, interviews and documentation. Then data analysis techniques such as data reduction, data presentation and drawing conclusions. The results of the study show that traders carry out buying and selling transactions based on Islamic business ethics where researchers find that there are still traders who prioritize honesty when trading (Gharar), sell merchandise consistently in the form of actual merchandise (Najasy) and traders say emphatically to all buyers not to be in debt (Al-’inah) because if it is done in debt it will make it difficult for traders to return to business capital.